2022
DOI: 10.1136/bmjresp-2022-001202
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil lymphocyte ratio as an indicator for disease progression in Idiopathic Pulmonary Fibrosis

Abstract: RationaleIdiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease. Patients present at different stages and disease course is varied. Blood monocytes have been linked to all-cause mortality, and neutrophils to progression to IPF in patients with the indeterminate for usual interstitial pneumonia CT pattern.ObjectiveTo determine association between blood monocytes, neutrophils and lymphocytes levels (and their derived indexes), with lung function decline and mortality in IPF.MethodsWe performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…2 Blood monocyte levels also correlated with the extent of fibrosis on CT scan, 3 and Kreuter also found an association with a composite measure of IPF outcome (FVC decline, 6-minute-walk distance reduction, acute exacerbation and/or mortality). 4 Moreover, we and others found that the neutrophil:lymphocyte ratio is also a predictor of mortality and FVC decline, 5,6 and patients with higher levels of neutrophils were more likely to progress from indeterminate for UIP CT pattern to UIP pattern and a clinical diagnosis of IPF. 7…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…2 Blood monocyte levels also correlated with the extent of fibrosis on CT scan, 3 and Kreuter also found an association with a composite measure of IPF outcome (FVC decline, 6-minute-walk distance reduction, acute exacerbation and/or mortality). 4 Moreover, we and others found that the neutrophil:lymphocyte ratio is also a predictor of mortality and FVC decline, 5,6 and patients with higher levels of neutrophils were more likely to progress from indeterminate for UIP CT pattern to UIP pattern and a clinical diagnosis of IPF. 7…”
Section: Introductionmentioning
confidence: 69%
“…4,21 Our findings suggest that neutrophils may be a contributor to active accumulation of fibrosis in IPF, supported by previous findings of high neutrophils in bronchoalveolar lavage (BAL) of IPF patients, 22 and more recent findings of higher neutrophil:lymphocyte ratio in IPF patients with greater rates of FVC decline. 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, inhibition of neutrophil chemokine CXCL8 or lack of neutrophil elastase can reduce bleomycininduced pulmonary fibrosis (Gregory et al, 2015;Gschwandtner et al, 2017). Similarly, increased neutrophils are associated with decreased FVC and all-cause mortality in IPF patients (Achaiah et al, 2022). It has been reported that deletion of exon 18 of COL17A1 in mice leads to IL-17-related inflammatory responses in the skin and infiltration of eosinophils, neutrophils, T-cell and mast cells (Lindgren et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 156 patients with IPF, a high percentage of BALF neutrophils was an independent predictor of early mortality [ 8 ]. Recently published data have shown that blood neutrophilia is associated with a decline in forced vital capacity and all-cause mortality in IPF [ 9 ], and with progression to IPF in patients with an indeterminate computed tomography pattern for UIP [ 10 ].…”
mentioning
confidence: 99%